XENOPHOBIC HOSTILITY IN “NO ESCAPE”: A MULTIMODAL ANALYSIS - Muh. Mufli Mu'afi Muin; Akhmad Affandi (Faculty of Languages and Literature, Universitas Negeri Makassar, 2026)
Xenophobic hostility in film is constructed not only through spoken language but also through visual action, spatial organisation, character movement, and narrative context. Although hate speech has been widely examined in online communication, less attention has been given to the multimodal representation of hostility toward foreigners in fictional films. This study examines how xenophobic hostility is verbally framed and audiovisually represented in John Erick Dowdle’s No Escape (2015). Using qualitative multimodal textual analysis, the study analysed the film and a synchronized English subtitle file to verify dialogue, timestamps, identity targets, and relevant narrative contexts. Data were selected when foreign status or nationality was clearly connected to collective labelling, blame, threats, pursuit, exclusion, or violence. The analysis identified ten sequences, consisting of four verbal or reported-verbal manifestations and six audiovisual manifestations. Verbal hostility was represented through the collective identification of foreigners, a reported collective death threat, the slogan “Blood for water,” and the directed threat “Find you, I kill you.” Audiovisual hostility appeared through the invasion of the hotel, physical targeting of foreign occupants, rooftop confinement, forced displacement, exclusion from safe public space, sustained pursuit, and coercive violence. The findings show that the film develops xenophobic hostility as a narrative progression from political-economic grievance and collective blame to individual targeting, spatial exclusion, and physical violence. The study concludes that multimodal analysis is necessary for distinguishing hostile speech from related visual and behavioural manifestations in film.